Communication—Microfluidic Electrochemical Acetylcholine Detection in the Presence of Chlorpyrifos. Issue 16 (1st January 2019) - McClain, Ethan S.; Miller, Dusty R.; Cliffel, David E.
Abstract : An amperometric acetylcholine sensor was developed for use in a microfluidic system and characterized with chlorpyrifos and its metabolite, chlorpyrifos oxon. This enzymatic sensor was highly selective for acetylcholine, with a detection limit of 0.2 μM and sensitivity of 1.7 nA μM −1 from 1–150 μM. Though chlorpyrifos had no effect on sensor function, chlorpyrifos oxon significantly inhibited response across a range of concentrations (0.5–50 μM). Inhibition was reversed by 2-pyridine aldoxime methyl chloride. This platform can be used to both quantify acetylcholine in the presence of chlorpyrifos and as a biorecognition method for chlorpyrifos oxon.